IMPLEMENTASI KEBIJAKAN PENURUNAN KASUS STUNTING DI KOTA SAMARINDA - Furqan Septianto, Achmad; Lituhayu, Dyah; Larasati Setianingsih, Endang (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Stunting is a serious public health problem, especially in children under five, which can have an impact on physical growth and suboptimal cognitive development. The city of Samarinda faces serious challenges related to the high stunting rate, requiring an effective policy response from the local government. This study aims to analyze the implementation of the policy to reduce stunting cases carried out by the Samarinda City Health Office. In an effort to reduce stunting in Samarinda City, the Government issued a regulation through Mayor Regulation No. 102 of 2021 concerning Stunting Reduction in Semarang City and became a guideline in this study. The purpose of this study is to analyze the process of policy implementation and the driving and inhibiting factors for the reduction of stunting in Samarinda City. This research uses a descriptive – qualitative method with data collection through observation, interviews, and documentation. The Samarinda City Health Office has been done well, by holding a program to increase nutritional awareness and understanding of the importance of balanced food consumption patterns, making several programs to reduce the Stunting Prevalence rate in Samarinda City such as GERMAS (Healthy Community Movement), ISIPIRINGKU, and then there is for adolescents, namely Nutrition Action. resources, disposition and bureaucratic structure. Researchers suggest to improve Holding periodic training for health workers and policy implementers, Equipping health centers and posyandu with adequate and modern health equipment to support better health services.